Acidosis significantly alters immune checkpoint expression profiles of T cells from oesophageal adenocarcinoma patients - Lysaght, Joanne; Ravi, Narayanasamy; Reynolds, John; Conroy, Melissa (My University, 2023)
Tumour acidosis contributes to cancer progression by inhibiting anti-tumour immunity. However, the effect of acidosis on anti-tumour T cell phenotypes in oesophageal adenocarcinoma (OAC) is unknown. Therefore, this study investigated the effect of acidosis on anti-tumour T cell profiles and if immune checkpoint blockade (ICB) could enhance anti-tumour T cell immunity under acidosis. Acidic conditions substantially altered immune checkpoint expression profiles of OAC patient-derived T cells, upregulating TIM-3, LAG-3 and CTLA-4. Severe acidosis (pH 5.5) significantly decreased the percentage of central memory CD4+ T cells, an effect that was attenuated by ICB treatment. ICB increased T cell production of IFN-γ under moderate acidosis (pH 6.6) but not severe acidosis (pH 5.5) and decreased IL-10 production by T cells under severe acidic conditions only. A link between lactate and metastasis was also depicted; patients with nodal metastasis had higher serum lactate levels (p = 0.07) which also positively correlated with circulating levels of pro-angiogenic factor Tie-2. Our findings establish that acidosis-induced upregulation of immune checkpoints on T cells may potentially contribute to immune evasion and disease progression in OAC. However, acidic conditions curtailed ICB efficacy, supporting a rationale for utilizing systemic oral buffers to neutralize tumour acidity to improve ICB efficacy. Study schematic-PBMCs were isolated from OAC patients (A) and expanded ex vivo for 7 days using anti-CD3/28 +IL-2 T cell activation protocol (B) and further cultured for 48 h under increasing acidic conditions in the absence or presence of immune checkpoint blockade (nivolumab, ipilimumab or dual nivolumab + ipilimumab) (C). Immunophenotyping was then carried out to assess immune checkpoint expression profiles and anti-tumour T cell phenotypes (D). Serum lactate was assessed in OAC patients (E-F) and levels were correlated with patient demographics (G) and the levels of circulating immune/pro-angiogenic cytokines that were determined by multiplex ELISA (H). Key Findings-severe acidic conditions upregulated multiple immune checkpoints on T cells (I). Efficacy of ICB was curtailed under severe acidic conditions (J). Circulating lactate levels positively correlated with circulating levels of pro-angiogenic factor tie-2 and higher serum lactate levels were found in patients who had nodal metastasis (K).
PUBLISHED
Keywords: A2aR; Acidosis; Immune checkpoints; Lactate; Oesophageal adenocarcinoma; Tie-2; Cancer; Immunology, Inflammation & Infection; CANCER; Tumour immunology and immunotherapy